THE POSSIBILITIES OF COENZYME Q10 AS PART OF THE COMPLEX THERAPY OF PATIENTS WITH CHRONIC HEART FAILURE - Yarmukhamedova Saodat Khabibovna; Gafforov Xudoyor Xudoyberdiyevich (Journals Park Publishing, 2024)
The aim of the study was to study the effect of coenzyme Q10 as part of the complex therapy of patients with chronic heart failure (CHF) on quality of life in comparison with traditional therapy without the addition of coenzyme Q10. The study included 75 patients with CHF 1-3 FC, which complicated the course of coronary heart disease (CHD) with a history of myocardial infarction. In a comparative aspect, the dynamics of the physical and psychological components of the quality of life of patients with CHF 1-3 FC under the influence of traditional therapy and traditional therapy with the addition of Coenzyme Q10. The quality-of-life indicators determined on the basis of the EQ-5D-DL and SF-36 questionnaires, complementing the picture of the disease, are a multifactorial criterion for assessing the condition of patients with CHF 1-3 FC. The improvement in quality of life is more pronounced under the influence of traditional therapy with the addition of coenzyme Q10.
Keywords: coenzyme Q10, coronary heart disease, quality of life, chronic heart failure.